Inside Cover: Chemistry of Tertiary Carbon Center in the Formation of Congested C−O Ether Bonds (Angew. Chem. Int. Ed. 8/2021). Issue 8 (4th January 2021) - Hirata, Goki; Takeuchi, Kentarou; Shimoharai, Yusuke; Sumimoto, Michinori; Kaizawa, Hazuki; Nokami, Toshiki; Koike, Takashi; Abe, Manabu; Shirakawa, Eiji; Nishikata, Takashi
Abstract : A stereospecific nucleophilic substitution between tertiary alkyl bromides and tertiary alkyl alcohols is described in the Research Article on page 4329 by Toshiki Nokami, Takashi Koike, Manabu Abe, Eiji Shirakawa, Takashi Nishikata, and co‐workers. The entering alcohol formally attacks the C−Br bond to undergo a retentive substitution with formation of tertiary alkyl ethers.